Optimizing sport environments to support athlete mental health - Henriksen, K. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
While physical prowess and performance have historically dominated the discourse surrounding athletic excellence, the significance of athlete mental health in optimizing athletic performance and overall welfare is increasingly recognized. Today, we agree that mental health is a core component of any culture of excellence, but it is also complex, and key stakeholders in elite sport struggle to negotiate their roles and responsibilities in promoting it. The majority of research in athlete mental health has taken an individual perspective and looked at the prevalence of specific disorders, individual risk and protective factors, coping strategies and evidence based methods of treatment. Although very important, this research cannot stand alone, because athlete mental health is not an individual affair. Indeed, sport environments can nourish or malnourish athlete mental health and influence help-seeking behaviour and stigma processes (Henriksen, Schinke, McCann et al., 2020). In this talk, I will invite you to look beyond the individual athlete and understand how athletes` mental health is very linked to the environments in which they train and compete. The recently published Team Denmark applied model of mental health (Henriksen, Diment et al., 2023) reveals layers of the environment - the training environment, leadership, everyday life, and cultural norms - that influence mental well-being. The model posits firstly that efforts to promote mental health should target all athletes and not only those that are languishing, and secondly that prevention, detection, and treatment processes should include all levels of the environment. The model provides stakeholders with a lens through which they can analyze, talk about, and optimize how their sport environments support the mental health of their athletes. Such a holistic and ecological perspective suggests that elite sport is not a win-at-all-costs endeavor. Rather, sports organizations should openly and critically review the degree to which their environment is a resource for their athletes` mental health.